Midwifery Care Baby In Diaper Rash in Pekanbaru Ernita BPM 2019: Midwifery Care Baby In Diaper Rash in Pekanbaru Ernita BPM 2019 - Widya Juliarti (Institute Of Computer Science (IOCS), 2020)
Diaper rash is a redness on baby's skin due to skin contact with a continuous diaper. About 50% of infants in diapers never experienced it. The purpose of this case study is to provide midwifery care in infants with diaper rash comprehensive and sustainable approach to obstetric management and documentation. Type of case study is descriptive. The case studies carried out in BPM Ernita in infants with diaper rash on July 1 to 8, 2019. The technique of collecting data through interviews, observation, and physical examination. Midwifery care in infants with diaper rash is done on an ongoing basis to monitor the patient's condition. Implementation of midwifery care do include fulfillment, personal hygiene baby. The results of the care that has been done four times the study of midwifery care, the baby's condition is good, rash wound is completely healed. Conclusion midwifery care using a midwifery management and documentation approach can address the problem and prevent sustainability. Implementation of midwifery care in infants with diaper rash is not a gap between theory and practice. Suggestions for BPM is expected after putting up the posters, people familiar with the symptoms of diaper rash in babies who wear diapers.